(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
India is a significant exporter of several handicrafts to the global market. The Indian Chikankari industry holds significant prominence in the global handicraft sector. This is one of India’s oldest cultures and traditions, which showcases many traditional arts from different regions of the nation. Chikankari items have a vast global market due to their increasing possibilities. The Indian Chikankari sector is characterized by its great reliance on manual labor and its decentralized nature, with production units located in both rural and urban locations across the country. The sector employs approximately six million craftspeople, many of them are women and individuals from marginalized communities. The Chikankari Sector has a substantial and crucial impact on the economy of the country. The craft industry in rural and semi-urban regions offers job opportunities to a significant number of artisans and contributes significantly to the country’s foreign exchange earnings, all while safeguarding its cultural legacy. Chikankari possess immense potential since they are crucial for supporting the current population of craftsmen located throughout the whole country. However, there are several challenges linked to the extensive growth of the Chikankari industry. The study emphasized the difficulty and many challenges linked to the Chikankari sector in India.